Pengembangan Budidaya Ikan Lele Clarias gariepinus INTENSIF Berbasis Teknologi Bioflok di Kelurahan Liabuku Kota Baubau Provinsi Sulawesi Tenggara: Development of Intensive Catfish (Clarias gariepinus) Culture Based on Biofloc Technology in Liabuku Village, Baubau City, Southeast Sulawesi Province - Sumitro Sumitro; Said Saleh Salihi; Budiyanti Budiyanti; Supasman Emu; Tamar Mustari; Wa Ode Safia; Wardha Jalil; Arfan Afandi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The cultivation of catfish Clarias gariepinus is very promising to be developed in Baubau City. However, the practice of catfish culture by farmers is still conventional, and the impact on catfish production results obtained by fish farmers is relatively low. The strategy is to develop intensive catfish culture using biofloc technology. This community service activity aims to provide farmers with knowledge regarding intensive catfish farming using the biofloc system. The method of this program is carried out using socialization of the program and the practice of catfish culture using the biofloc system. This activity results in farmers creating biofloc ponds, culture flocks, calculating carbon requirements, managing water quality, feed management, and disease control.